Complexos de vanádio contendo bases de Schiff como catalisadores na oxidação do cicloexano - Cantanhede, Leonardo Baltazar (Universidade Federal de São Carlos, 2014)
The vanadium complexes of the type [VO(acac)2], [VO(acac)(apftsc)], [VO(acac)(apmtsc)], [VO(acac)(aptsc)], [VO(acac)(apf)], vanadium (IV) and [VO2(apftsc)], [VO2(apmtsc)], [VO2(aptsc)] e [VO2(apf)], vanadium (V), were used as catalysts for cyclohexane oxidation using 30% hydrogen peroxide (H2O2) as oxidizing agent in acetonitrile at 40ºC. The cyclohexanol (OL) and cyclohexanone (ONA) were quantified by means of gas chromatography by the internal padronization method. Variation in the molar ratio of oxidizing, substrate and nitric acid with catalyst, as well as the effect of the addition of triphenylphosphine in catalytic properties were studied for all complexes. For the complex [VO(acac)(apftsc)], yielded the kinetic parameters with rate constant (k = 3,87 x 10-1 L.mol-1.min-1), reaction order relative to catalysts (nCat = 0,8) and to substrate (nS = 0,6); the thermodynamic parameters of activation Eap = 11 kcal.mol-1, ΔG# = + 0.6 kcal.mol-1, ΔH# = + 10.2 kcal.mol-1, ΔS# = + 30.8 cal.mol-1.K-1. The EPR spectrum data using 5,5-dimethyl-1-pyrroline Noxide (DMPO) as spin trap confirm that the mechanism the formation of radicals. The radicals ( acac) and hydroxyl ( OH) from the acetylacetonate e and hydrogen peroxide, respectively, was identified by forming the respective adduct, DMPO-Acac and DMPO-OH. From the mass spectrometry data it was possible to suggest a synthetic route for the formation of the oxo(peroxo)vanadate complex, an important intermediate in the catalytic cycle. It has been proposed also a mechanism for cyclohexane oxidation.
Vanadium complexes as catalysts for the oxidation of cyclohexane
Keywords: Catálise; Complexos de vanádio; Hidrocarbonetos - oxidação; Cicloexano; CIENCIAS EXATAS E DA TERRA::QUIMICA